UPAYA GURU DALAM MENINGKATKAN MINAT BELAJAR SISWA KELAS II PADA TEMA 2 MELALUI MEDIA ORIGAMI DI SD MUHAMMADIYAH INDONESIANA TIDORE - Julita Idrus; Devi Wahyu Ertanti; Mutiara Sari Dewi (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2020)
In the learning process  in the classroom  students often come in and out of class, chat  with their peers,  are passive  when learning, even in terms of answering,  questions, they have  low abilities  and  there are students  wholl diffcult to  write,  read  and  do assignments given by the  teacher. This research  is a  learning  approach that connects various subjects that reflect the real world around them and within the ran  e of abilities, student development and increase student  interest in learning.  The objectives mentioned above are carried out with this type of qualitative  research,  in this study the authors  use two data sources,  namely data sources, primary  and secondary data. Interviews aimed directly at homeroom  teachers of class II, principals and teachers at  SD Muhammadiyah Indonesiana  Tidore  using  interview  guidelines   with  the  aim  of obtaining data  about teacher efforts, constraints, solutions  in increasing student  interest in grade Il on theme 2 playing in my environment  through origami media. Increase student interest in learning through  an interesting medium,  namely origami media  that can attract  visual eyes and fine motor skills and can increase students  'interest and right brain  intelligence,  aims to broaden students' insight and be creative in their own creations with guidance by teachers in learning interest can make students able follow the  learning process  well.